African American Women in the Oprah Winfrey Network's Queen Sugar Drama: Exemplary Representations On Screen and Behind the Scenes - Jefferson, Ollie L. (Lexington Books, 2021)
This critical study interrogates the intersection of race and gender media representations on screen and behind the scenes. The thought-provoking investigation on the Oprah Winfrey Network’s Queen Sugar series shows the ways in which the television drama is a significant contribution to mainstream media that creates in-depth conversations concerning African American women’s social roles, social class, and social change. Ollie L. Jefferson provides a unique analysis of the television production by using the exemplary representations conceptual framework to contextualize and theorize research contributing to systemic change. Jefferson highlights the best practices used by African American female executive producers, Oprah Winfrey and Ava DuVernay, by examining Queen Sugar as a case study. The investigation shows how the decision-makers produced multidimensional female characters to illustrate the complex humanity of Black lives. This book broadens understanding of the media industry’s need for culturally sensitive and conscious inclusion of women and people of color behind the scenes—as media owners, creators, writers, directors, and producers—to put an end to the persistent and pervasive misrepresentations of African American women on screen. Scholars of television studies, film studies, media studies, race studies, and women’s studies will find this book particularly useful.